Analysis of the Effect of Using OT Link Application at PT. Arta Boga Cemerlang DKI Jakarta Area - Utomo, Mohammad Nurrizqi Putro; Ardianto, Yusaq Tomo; Respati, Harianto (International Journal Labs, 2024)
The demands of company needs are increasingly complex and require the application of appropriate information technology to help meet company needs. PT. Arta Boga Cemerlang launched the OT Link application which is used to meet company needs in accelerating the dissemination of information related to work results and important company information. The OT Link application can be used on smartphone devices with Android and iOS software, making it easier to access. This research is explanatory research, the location of this research was carried out in DKI Jakarta. The population in this study were all people who used the OT Link application with a sample size of 160 respondents. Data collection by distributing questionnaires online via social networks owned by the company. Data analysis techniques use Descriptive Statistical Analysis, Data analysis uses path analysis, and Hypothesis Testing. The results of this research are that information quality and service quality affect user satisfaction, user satisfaction has an effect on net benefits, and system quality has no affect on user satisfaction, and system quality, information quality, and service quality have no affect on net benefits through user satisfaction of the OT Link application.